2020
DOI: 10.21203/rs.3.rs-34643/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-distance airborne dispersal of SARS-CoV-2 in COVID-19 wards

Abstract: Abstract Evidence suggests that SARS-CoV-2 can be dispersed and potentially transmitted by aerosols, directly or via ventilation systems. We report detection of SARS-CoV-2 RNA in COVID-19 ward ceiling vent openings as well as in ventilation exhaust filters and central ducts up to at least 56 meters from patient areas. As this ventilation system provides low air flow, we propose that viral particles may be readily dispersed in air over vast distances and that further inv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 13 publications
3
83
1
Order By: Relevance
“…RNA was extracted using the Direct-zol™-96 RNA kit according to the manufacturer's protocol (Zymo Research, USA). The Envelope (E) gene was quantified by the RT-qPCR assay as described previously [ 3 , 15 ]. The primer pair and probe were based on sequences published by Corman et al [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted using the Direct-zol™-96 RNA kit according to the manufacturer's protocol (Zymo Research, USA). The Envelope (E) gene was quantified by the RT-qPCR assay as described previously [ 3 , 15 ]. The primer pair and probe were based on sequences published by Corman et al [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the current available information, we are unable to determine the full influence of these significant factors. Nissen et al (2020) found viral signal in air vents and filters meters away from patients in a low relative humidity environment (approximately 30%), but they could not detect growth or infectivity, and hypothesized that the virus may have been inactive due to desiccation of the pathogen in the vents. Recent studies have shown a variability in the survivability of the virus in surfaces, depending on the material, temperature, relative humidity, and light, with all of these factors playing an important role (Riddell et al, 2020;Van Doremalen et al, 2020;Wolff et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have shown that COVID-19 patients can produce aerosols laden with viable SARS-CoV-2, even though no aerosol-generating procedure is in place 45 , and that these can travel long distances in hospital wards through ventilation 46 . This confirms the fact that the virus can be potentially transmitted via aerosols and that this must be taken into account when assessing preventive measures.…”
Section: Discussionmentioning
confidence: 99%